Colonoscopic Review and Surgical Approach in the Management of Colorectal Carcinoma–A Retrospective Study of 50 cases - Quadir, Md Ershad ul; Rahman, Munshi Md Mojibur; Rahman, Md Mahbubur (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: There is no exact statistics about the incidence of colorectal cancer in Bangladesh. According to National Cancer Institute, London, it is the 2nd most common cancer affecting more than 30,000 people in each year. As many patients with colon cancer do not develop symptoms until it is advanced and detection in early stage can only be achieved by screening of asymptomatic person. Maximum patients present lately with distance metastases when there is nothing to treat except palliative therapy. Objectives: To identify the risk factors, early symptoms, signs, treatment modalities, operative outcome, morbidity and mortality rate. Materials and Methods: This retrospective study was carried out at CMH Dhaka during August 2002 to August 2004. A total of 50 patients were taken as study sample. All the patients were admitted in different surgical units of CMH Dhaka for surgical treatment. Detailed history were taken on admission by a questionnaire and examined thoroughly and findings regarding Anaemia, Jaundice, Dehydration, Oedema, Lymphadenopathy, Nutritional status and abnormal signs like ascites, distension, rigidity, organomegaly recorded. Digital rectal examination were done in all cases and finally examined by Proctoscope, Sigmoidoscope and with Colonoscope. FOBT (Fecal Occult Blood Test), serum tumour marker was also assessed. Results: Out of 50 cases 22 were rectal carcinoma and next common site was caecum and number was 10. There was a variation in the sex ratio. Out of 50 cases 33 were male and 17 were female. The highest incidence was among people of 6th decade (28%) and next highest was in 4th decade (24%). Majority of patient with right colon cancer presented with abdominal pain 12 out of 22 cases (56%) and weight loss 15 cases (68%). For left colon cancer commonest symptom was weight loss and weakness and altered bowel habit. Almost all cases with rectal carcinoma presented with bleeding per rectum. Conclusion: About 50% of lesions were found in recto-sigmoid junction and male: female ratio was 1.9:1. All efforts and modern technology should be applied for early detection and treatment. The survival rate is usually very poor in rectal carcinoma. In this study most of the cases were subjected to post operative Chemo and Radiotherapy, but more were treated with neoadjuvant chemoradiation for down staging. The need for early detection of Colorectal Carcinoma (CRC) should be stressed in the form of screening patient awareness and understanding about symptomatology. Early diagnosis and definitive treatment are thereby increasing expectation of higher survival and better prognosis in patient of colorectal carcinoma. Journal of Armed Forces Medical College Bangladesh Vol.11(2) 2015: 36-40